The Online Operating time Management System - Hareasang, Wachara (Research and Development Journal Sisaket Rajabhat University, 2020)
The research aims to a development for management personnel attendance online system. Researcher has studied and developed the system by data flow diagram, database relationship (E-R Diagram) is a tool for system design and using PHP language, MySQL is a database program. System satisfaction assessment results the researcher determined the population of 66 people found that Satisfaction with web applications, management personnel attendance online system. The system can be used for practical purposes. From the assessment using questionnaires, divided into 3 parts. Get the following mean the satisfaction results in the usability of the system (Usability Test) mean 4.29, the evaluation is good. In terms of the security of information in the system (Security Test) the average is 4.22, the evaluation is good. Functionality according to the function of the system (Function Test), the average is 4.25, the evaluation is good. Keyword : Information Systems / Management